Neonatal External Description in Undiagnosed Placenta Accreta Referral Patients - Ilvira, Stivany; Ernawati, Ernawati; Lestari, Pudji (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background: Cases of placenta accreta are increasing every year. Placenta accreta has an impact on maternal and neonatal externals. There are cases of placenta accreta that go undiagnosed during pregnancy called undiagnosed. This study aims to find out the neonatal exterior in undiagnosed placenta accreta referral patients at dr. Soetomo Hospital in 2016-2020. Method: This research method is descriptive with an observational approach. The study sample was the entire infant of a patient with a referral case of undiagnosed placenta accreta using the total samplingtechnique. The variable studied was the neonatal exterior. Results: Samples that met the inclusion criteria of 27 infants. The termination age of preterm pregnancy was 8 (29.6%) patients, BBLR as many as 6 (22.2%) infants, female sex (55.6%), babies with SGA as many as 2 (7.4%) babies and LGA as many as 1 (3.7%) babies. APGAR scores less than 7 as many as 6 (22.2%) babies in the first minute and 2 (7.4%) babies in the fifth minute. Nicu resuscitation and care measures were 14 (51.9%) infants and 2 (7.4%) deaths. Conclusion: Neonatal discharge in patients undiagnosed placenta accreta includes potential premature birth, BBLR, resuscitation measures, NICU care, neonate mortality rate of 7.4%. There needs to be an improvement in the quality of ANC, especially in early detection of risk factors so that undiagnosed cases are reduced and betteroutcomes are obtained.